Targeting the Host Response: Can We Manipulate Extracellular Matrix Metalloproteinase Activity to Improve Influenza Virus Infection Outcomes? - Pedrina, Jess; Stambas, John (Frontiers in Molecular Biosciences, 2021)
Each year, hundreds of thousands of individuals succumb to influenza virus infection and its associated complications. Several preventative and therapeutic options may be applied in order to preserve life. These traditional approaches include administration of seasonal influenza vaccines, pharmacological interventions in the form of antiviral drug therapy and supportive clinical approaches including mechanical ventilation and extracorporeal membrane oxygenation (ECMO). While these measures have shown varying degrees of success, antiviral therapies and vaccination are constrained due to ongoing antigenic drift. Moreover, clinical approaches can also be associated with complications and drawbacks. These factors have led to the exploration and development of more sophisticated and nuanced therapeutic approaches involving host proteins. Advanaces in immunotherapy in the cancer field or administration of steroids following virus infection have highlighted the therapeutic potential of targeting host immune responses. We have now reached a point where we can consider the contribution of other “non-traditional” host components such as the extracellular matrix (ECM) in immunity. Herein, we will review current, established therapeutic interventions and consider novel therapeutic approaches involving the extracellular matrix.